Ordinary Hall anomaly due to the Fermi surface shape in MnAs - Helman, Christian (2021)
We analyze the influence of the Fermi surface (FS) shape on magnetotransport properties, particularly on the Hall effect in the MnAs compound. Evidence of opposite conduction polarities for different crystal directions (goniopolarity) and a strong dependence of carrier type has been observed in MnAs films with an applied magnetic field. To understand this behavior, we developed a semiclassical model together with the Boltzmann transport theory that takes into account both the applied magnetic field and the FS shape. The MnAs FS is obtained by means of density functional theory, showing a clear dominance of the hyperboloid shape. Our study corroborates that the specific topology of the Fermi surface gives rise to a goniopolar behavior in the Hall transport. These theoretical results are supported by magnetotransport measurements on MnAs thin layers epitaxially grown on GaAs(001) and on GaAs(111), allowing us to explore the transport characteristics for two different crystal directions of the system.